Lazy wave propagation. Issue 2 (3rd September 2018) - Boehm, Christian; Fichtner, Andreas
Summary: We introduce the concept of 'lazy wave propagation' for time-domain simulations of the wave equation, which means to locally skip the computation of the wavefield whenever it has no influence on synthetic measurements. This is a simple and efficient extension to conventional implementations, which becomes particularly powerful for sequentially simulating multiple sources with similar receiver locations. Lazy wave propagation utilizes the spatio-temporal localization of the wavefield and it takes advantage of the finite speed at which energy propagates through a medium. The key idea is to dynamically adjust the computational domain and to compute the wavefield only inside the region of influence of the source locations intersected with the domain of dependence of the receiver locations. This approach decreases the amount of floating-point operations to compute internal forces by up to 40  per cent for realistic source–receiver geometries. While our main focus is the 'lazy spectral-element method', the same ideas apply to discontinuous Galerkin, finite-volume or finite-difference methods.